2013
DOI: 10.2174/1871527311312030012
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Molecules in CNS Disorders: Biomarker and Therapeutic Targets

Abstract: Mounting evidence has been provided regarding the crucial role of leukocyte extravasation and subsequent inflammatory response in several central nervous system (CNS) disorders. The infiltrated leukocytes release pro-inflammatory mediators and activate resident cells, leading to tissue injury. Leukocyte-endothelia interaction is critical for leukocyte extravasation and migration from the intravascular space into the tissue during inflammation. The basic physiology of leukocyte-endothelia interaction has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 150 publications
(175 reference statements)
1
18
0
Order By: Relevance
“…3,4 Several interacting endothelial cell mediators including nitric oxide (NO), vascular endothelial growth factor (VEGF), and vascular cell adhesion molecule-1 (VCAM-1) were implicated in several neuronal effects including cell proliferation, angiogenesis, inflammation, and neurological impact on glial and neuronal cells. 5,6 AD was associated with increased vascular inflammation, as evidenced by elevated expression and localization of inflammatory markers such as VCAM-1 and Tumor necrosis factor-a (TNF-a) surrounding AD-plaques. 7 Previous studies reported that decline in VEGF-A was correlated with the aggravation of AD pathology indicated by the high level of a-synuclein.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several interacting endothelial cell mediators including nitric oxide (NO), vascular endothelial growth factor (VEGF), and vascular cell adhesion molecule-1 (VCAM-1) were implicated in several neuronal effects including cell proliferation, angiogenesis, inflammation, and neurological impact on glial and neuronal cells. 5,6 AD was associated with increased vascular inflammation, as evidenced by elevated expression and localization of inflammatory markers such as VCAM-1 and Tumor necrosis factor-a (TNF-a) surrounding AD-plaques. 7 Previous studies reported that decline in VEGF-A was correlated with the aggravation of AD pathology indicated by the high level of a-synuclein.…”
Section: Introductionmentioning
confidence: 99%
“…sICAM-1 is an endothelial and leukocyte associated transmembrane protein renowned for its role in maintaining cell-cell interactions and promoting leukocyte endothelial transmigration. Activated endothelium releases soluble adhesion molecules and is therefore used to measure endothelial activation by measuring fluid-phase of those molecules(20). Previous study reported that another saffron compound, crocetin, can reduce leukocyte adhesion to endothelial cells by decreasing the expression of ICAM-1(18).…”
Section: Discussionmentioning
confidence: 99%
“…They are low expressed mainly by endothelial cells under normal condition. In the inflammatory process, the expression of these adhesion molecules can be upregulated to promote leukocyte adhesion and blood-derived monocytes transmigration [43]. The upregulation of these molecules has been identified to participate in numerous neurological disorders [4446].…”
Section: Discussionmentioning
confidence: 99%